Astronomically forced climate change during the Middle Oligocene-Early Miocene in the Pearl River Mouth Basin, Northern South China Sea - Shizhen Jia; Yanzhen Li; Mengqing Shang; Rui Liu; Linzhen Hu; Yongming Zhang; Xiuju Xing; Zi’ang Yang (Marine Geophysical Research, 2026)

METTL18-catalyzed histidine methylation of YTHDF2 promotes mRNA stability - Wen-Lan Yang; Meng-Xia Liu; Yue Han; Xing-Xing Li; Ye Gu; Xinyuan Tian; Mengqian Mu; Xiaolin Zhang; Yanzhe Wang; Xinyu Li; Yu-Sheng Chen; Chun-Chun Gao; et al. (Science China Life Sciences, 2026)

Interactive effects of noise and odor on construction workers' environmental perception and cognitive performance amid outdoor thermal stress - Zi Li; Xinyue Zhang; Zijing Peng; Ran Xing; Ang Li; Bo Hong (Building and Environment, 2026)

Physical exercise protects cardiovascular fitness in long-term spaceflight: what have we learned? - Zi’ang Zhang; Wenjuan Xing; Guiling Wu; Xing Zhang; Jia Li; Yingxian Li; Feng Gao (Science China Life Sciences, 2026)

Dynamic Response and Operational Performance of an Integrated Floating Wind Turbine–Net Cage Platform - Xing-Hua Shi; Qiang Ang; Jing Zhang; Honglong Li; Chunhan Wu; Shan Wang (Journal of Marine Science and Engineering, 2026)
This study investigates the floating wind turbine (FWT)–Net cage integrated platform, where the net cage is rigidly connected to the FWT foundation. The platform is numerically modeled using time-domain simulations in OrcaFlex V11.1, based on representative environmental conditions of the South China Sea. The operational performance of two layouts of the platform is evaluated and compared, considering both power generation efficiency and residual volume ratio as key indicators. The results show that the FWT–Net cage integrated platform exhibits superior hydrodynamic stability, characterized by reduced surge and pitch motions, lower mooring force fluctuations, and a higher residual cage volume. Additionally, the platform achieves better power generation efficiency and a higher residual volume ratio, indicating more effective use of the aquaculture space. Based on these findings, an improved integrated design incorporating additional outer net cages is proposed. This design demonstrates enhanced aquaculture capacity while maintaining power generation. The results provide valuable insights for the design of FWT–Net cage integration, promoting the efficient and sustainable utilization of marine space.

Isolation and identification of spoilage bacteria from kiwifruit and analysis of the antagonistic activity of three Bacillus strains against these bacteria - Ang Liu; Wen-xin Li; Yi Liu; Xing-lin Ran; Bo-yu Dong; Qiu-ping Yao; De-quan Zhu (Food Control, 2026)

Metals and polycyclic aromatic hydrocarbons co-exposure: Amino acid omics insights on blood glucose homeostasis - Jiaxin Zhao; Ming Yang; Xiaoqing Xing; Yayuan Mei; Quan Zhou; Meiduo Zhao; Jing Xu; Yanbing Li; Kai Li; Qun Xu; Ang Li (Journal of Environmental Sciences, 2025)

Estimating rainfall intensity from surveillance audio: A hybrid model-data-driven framework - Xing Wang; Kun Zhao; Haiqin Chen; Ang Zhou; Jiuwei Zhao; Shuaiyi Shi; Thomas Glade (Journal of Hydrology, 2025)

Standing at the crossroads: How does amino acids function in the crosstalk between pancreas and the kidney under exposure to per- and polyfluoroalkyl substances? - Ming Yang; Ziwen An; Xiaoqing Xing; Yayuan Mei; Haoran Li; Jiaxin Zhao; Zhenzhen Tan; Yanbing Li; Jingjing Zhao; Jiayin Zhao; Meiduo Zhao; Jing Xu; et al. (Journal of Hazardous Materials, 2025)

Transmission of ultrasonic wave across moisture rocks: Effects of moisture sorption on velocity variation and attenuation - Ang Liu; Guijie Sang; Shimin Liu; Xing Li; Gang Wang (International Journal of Rock Mechanics and Mining Sciences, 2025)

Changes in grassland types caused by climate change and anthropogenic activities have increased carbon storage in alpine grassland ecosystem - Min Zhang; Ang Chen; Xiaoyu Xing; Dong Yang; Zichao Wang; Xiuchun Yang (Global and Planetary Change, 2025)

Ketamine Alters Specific Gene Expression Profiles by Transcriptome-Wide Responses in a Ketamine-Induced Schizophrenia-Like Mouse Model - Zhe Du; Xiu-mei Zhu; Peng Lv; Ying Pan; Xi-kai Hou; Ang Li; Dong Zhao; Jia-xin Xing; Jun Yao (Molecular Neurobiology, 2025)

Intelligent real-time status identification for anti-roll tank via solid-liquid triboelectric nanogenerators - Xing'ang Xu; Hao Wu; Zhongjie Li; Siyu Jia; Shuaitao Jin (Ocean Engineering, 2025)

Estimation of crude protein content in natural pasture grass using unmanned aerial vehicle hyperspectral data - Huimin Qi; Ang Chen; Xiuchun Yang; Xiaoyu Xing (Computers and Electronics in Agriculture, 2025)

Visible light-powered photodynamic antibacterial chlorophyllin-derived metallochlorins - Yuling Xue; Kuoran Xing; Max Jing Rui Tham; Bang Lin Li; Narattam Sikdar; Lai Peng Leong; Ching Hua Lee; Justin Jang Hann Chu; Wee Han Ang; David Tai Leong (Chemical Engineering Journal, 2025)

Methane emissions from the riverine sandy wetlands on the Mongolia Plateau - Ang Li; Zun-Lan Luo; Katerina Machacova; Song Zhao; Jin-Chao Feng; Xing-Guo Han; Zhi-Ping Wang (Environmental Monitoring and Assessment, 2024)

High valent manganese-oxo species activation of peroxymonosulfate by different phases manganese oxides nanoplates for catalytic water decontamination - Ang Li; Bin Li; Li-Ming Sun; Le-Xuan Liu; Chang Liu; Ya-Meng Dong; Xing Zhang (Chemical Engineering Journal, 2024)

New formula of vegetation roughness height and Darcy–Weisbach friction factor in channel flow - Da-Qian Feng; Jing-Jing Fan; Wei-Jie Wang; Cheng-Xing Xia; Ang Li (Journal of Hydrology, 2024)

Cross-scale mapping of above-ground biomass and shrub dominance by integrating UAV and satellite data in temperate grassland - Ang Chen; Cong Xu; Min Zhang; Jian Guo; Xiaoyu Xing; Dong Yang; Bin Xu; Xiuchun Yang (Remote Sensing of Environment, 2024)

Development and evaluation of a haplotype reference panel of Zhikong scallop (Chlamys farreri) for genotype imputation - Mingyi Sui; Zhi Liu; Xiaowen Huang; Zujing Yang; Haitao Yu; Chang Cui; Yuqing Hu; Xuefeng Wang; Xiaojing Shen; Qianqian Mu; Mingxuan Teng; Ang Zhao; et al. (Aquaculture, 2024)

Biochar and microorganism assisted phytoremediation of severely molybdenum-contaminated soil: Efficacy, mechanisms and the impact of low temperatures - Chunyan Li; Jie Xing; Qian Xu; Di Cui; Yuqing Liu; Changlong Pang; Ang Li (Journal of Cleaner Production, 2024)

Dynamic monitoring of aboveground biomass in inner Mongolia grasslands over the past 23 Years using GEE and analysis of its driving forces - Dong Yang; Zhiyuan Yang; Qingke Wen; Leichao Ma; Jian Guo; Ang Chen; Min Zhang; Xiaoyu Xing; Yixin Yuan; Xinyu Lan; Xiuchun Yang (Journal of Environmental Management, 2024)

Fault diagnosis of marine machinery via an intelligent data-driven framework - Xing'ang Xu; Yan Lin; Chao Ye (Ocean Engineering, 2023)

Multi-omics analyses reveal relationships among polyphenol-rich oolong tea consumption, gut microbiota, and metabolic profile: A pilot study - Ang Li; Ruixin Kou; Haiwei Liu; Mengshan Chen; Jin Wang; Qisijing Liu; Xiaolong Xing; Bowei Zhang; Lu Dong; Shuo Wang (Food Chemistry, 2023)

Prospects and perspectives on advanced materials for sodium-ion batteries - Zhen-Yi Gu; Xiao-Tong Wang; Yong-Li Heng; Kai-Yang Zhang; Hao-Jie Liang; Jia-Lin Yang; Edison Huixiang Ang; Peng-Fei Wang; Ya You; Fei Du; Xing-Long Wu (Science Bulletin, 2023)

Re-Exploring the Inflammation-Related Core Genes and Modules in Cerebral Ischemia - Wenjing Lv; Junqi Jiang; Yi Xu; Zhiyuan Chen; Zixuan Wang; Ang Xing; Xueping Zheng; Tingting Qu; Qi Wan (Molecular Neurobiology, 2023)

Isolation and identification of the molybdenum-resistant strain Raoultella ornithinolytica A1 and its effect on MoO42− in the environment - Jie Xing; Chunyan Li; Wanting Li; Xuemei Zhang; Zhaoquan Li; Ang Li (Biodegradation, 2023)

scRNA-seq analysis reveals toxicity mechanisms in shrimp hemocytes subjected to nitrite stress - QingJian Liang; BeiBei Dong; Ang Li; LiTing Wu; Yu Zhang; Tao Han; Xing Liu (Chemosphere, 2023)

Submerged macrophytes mediated remediation of molybdenum-contaminated sediments - Jie Xing; Chunyan Li; Zhaoquan Li; Wanting Li; Ailun Fang; Ang Li (Environmental Science and Pollution Research, 2023)

Characterization and shifting of microbial community to denitrification for anaerobic sulfamethoxazole biodegradation with different electron acceptors - Xiaoli Su; Feiyun Sun; Jianjun Zhang; Dingyu Xing; Xiaoying Li; Zi Song; Liang Feng; Zhichao Huang; Ang Li (Journal of Cleaner Production, 2023)

Response of ecosystem services in Beijing-Tianjin Sandstorm Source Control Project to differing engineering measures scenarios - Xiaoyu Xing; Xiuchun Yang; Jian Guo; Ang Chen; Min Zhang; Dong Yang; Zhiyan Hou; Huilong Zhang; Xing Wang (Journal of Cleaner Production, 2023)

Advanced layered oxide cathodes for sodium/potassium-ion batteries: Development, challenges and prospects - Zhi-Xiong Huang; Zhen-Yi Gu; Yong-Li Heng; Edison Huixiang Ang; Hong-Bo Geng; Xing-Long Wu (Chemical Engineering Journal, 2023)

Phylogenomic Analyses of a Clade Within the Family Flavobacteriaceae Suggest Taxonomic Reassignments of Species of the Genera Algibacter, Hyunsoonleella, Jejuia, and Flavivirga, and the Proposal of Pseudalgibacter gen. nov. and Pseudalgibacter alginicilyticus comb. nov. - Miao Li; Ling-Zhi Hou; Xing-Hao Xu; Xiao-Xiao Wang; Ming-Can Zheng; Yan-Jiao Zhang; Ang Liu (Current Microbiology, 2021)

HLA in Alzheimer’s Disease: Genetic Association and Possible Pathogenic Roles - Zi-Xuan Wang; Qi Wan; Ang Xing (NeuroMolecular Medicine, 2020)

Safety, pharmacokinetics, and pharmacodynamics of BMS-986142, a novel reversible BTK inhibitor, in healthy participants - Sun Ku Lee; Jun Xing; Ian M. Catlett; Robert Adamczyk; Amber Griffies; Ang Liu; Bindu Murthy; Miroslawa Nowak (European Journal of Clinical Pharmacology, 2017)

The Role of MAPT in Neurodegenerative Diseases: Genetics, Mechanisms and Therapy - Cheng-Cheng Zhang; Ang Xing; Meng-Shan Tan; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2016)

The Role of Cdk5 in Alzheimer’s Disease - Shu-Lei Liu; Chong Wang; Teng Jiang; Lan Tan; Ang Xing; Jin-Tai Yu (Molecular Neurobiology, 2016)

Transcript analysis of citrus miRNA397 and its target LAC7 reveals a possible role in response to boron toxicity - Long-Fei Jin; Yong-Zhong Liu; Xin-Xing Yin; Shu-Ang Peng (Acta Physiologiae Plantarum, 2016)

A Head-to-Head Comparison of the Antimicrobial Activities of 30 Ultra-Short Antimicrobial Peptides Against Staphylococcus aureus, Pseudomonas aeruginosa and Candida albicans - Qiu Ying Lau; Xing Yao Choo; Zhi Xue Lim; Xin Ni Kong; Fui Mee Ng; Melgious J. Y. Ang; Jeffrey Hill; C. S. Brian Chia (International Journal of Peptide Research and Therapeutics, 2015)

Low-intensity pulsed ultrasound-mediated stimulation of hematopoietic stem/progenitor cell viability, proliferation and differentiation in vitro - Peng Xu; Hilal Gul-Uludag; Woon T. Ang; Xiaoyan Yang; Min Huang; Leah Marquez-Curtis; Locksley McGann; Anna Janowska-Wieczorek; James Xing; Eric Swanson; Jie Chen (Biotechnology Letters, 2012)

Molecular cloning, characterization, and function analysis of a mevalonate pyrophosphate decarboxylase gene from Ganoderma lucidum - Liang Shi; Lei Qin; Yingjie Xu; Ang Ren; Xing Fang; Dashuai Mu; Qi Tan; Mingwen Zhao (Molecular Biology Reports, 2012)

Development of a simple and efficient transformation system for the basidiomycetous medicinal fungus Ganoderma lucidum - Liang Shi; Xing Fang; Mengjiao Li; Dashuai Mu; Ang Ren; Qi Tan; Mingwen Zhao (World Journal of Microbiology and Biotechnology, 2012)